Long-term neurodevelopment in children born with esophageal atresia: a systematic review. Issue 11 (10th August 2021) - van Hoorn, Camille E; ten Kate, Chantal A; Rietman, Andre B; Toussaint-Duyster, Leontien C C; Stolker, Robert Jan; Wijnen, Rene M H; de Graaff, Jurgen C
Summary: Background: Although the survival rate of esophageal atresia (EA) has increased to over 90%, the risk of functional long-term neurodevelopmental deficits is uncertain. Studies on long-term outcomes of children with EA show conflicting results. Therefore, we provide an overview of the current knowledge on the long-term neurodevelopmental outcome of children with EA. Methods: We performed a structured literature search in Embase, Medline Ovid, Web of Science, Cochrane CENTRAL, and Google scholar on November 8, 2020 with the keywords 'esophageal atresia', 'long-term outcome', 'motor development', 'cognitive development', and 'neurodevelopment'. Results: The initial search identified 945 studies, of which 15 were included. Five of these published outcomes of multiple tests or tested at multiple ages. Regarding infants, one of six studies found impaired neurodevelopment at 1 year of age. Regarding preschoolers, two of five studies found impaired neurodevelopment; the one study assessing cognitive development found normal cognitive outcome. Both studies on motor function reported impairment. Regarding school-agers, the one study on neurodevelopmental outcome reported impairment. Cognitive impairment was found in two out of four studies, and motor function was impaired in both studies studying motor function. Conclusions: Long-term neurodevelopment of children born with EA has been assessed with various instruments, with contrasting results. Impairments were mostly found in motor function, but also in cognitive performance. Generally, the long-term outcome of these children is reason for concern. Structured, multidisciplinary long-term follow-up programs for children born with EA would allow to timely detect neurodevelopmental impairments and to intervene, if necessary.